Elam in the era of the early dynasties (2750-2315 BC) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Multiple civilizations arose in the ancient Arab East, or what is known as Western Asia, which influenced the Mesopotamian civilization, one of the most important civilizations in the world. From the east, the ancient civilization of ElamConsidered by historians and archaeologists as an offspring of the Mesopotamian civilization, it originated and was influenced by it, until the civilization of Elam became very similar to the civilization of Mesopotamia, far from the history of what is known today as the Iranian plateau. What necessitated this connection between the two sides is the geographical unity that linked them. Elam was also a source for many of the raw materials that Mesopotamia Despite this, the civilization of Elam was not a civilization completely dependent on others, but rather it was self-contained.